SURG-37. NEURO-ONCOLOGICAL AUGMENTED REALITY: A MORE INTUITIVE APPROACH TO RESECTION PLANNING. (14th November 2022) - Van Gestel, Frederick; Frantz, Taylor; Neuville, Quentin; Klein, Sam; Bruneau, Michaël; Jansen, Bart; Scheerlinck, Thierry; Vandemeulebroucke, Jef; Duerinck, Johnny
Abstract: BACKGROUND: When preparing for the resection of an intracranial lesion, its borders and optimal approach are often determined using neuronavigation with a tracked pointer. This can sometimes prove challenging, especially for deep-seated lesions. Augmented reality (AR) can simplify and improve this step by directly displaying the lesion on the patient's skin. METHODS: A proprietary inside-out infrared tracking solution was developed, allowing for heads-up displaying AR scenes on the Microsoft HoloLens II without the need for an external tracking camera or computer. We included twenty patients with an intracerebral lesion planned for resection. After semi-automatic hologram-to-patient registration, different participants marked the lesion outlines on the patient's skin, consecutively aided by the Brainlab neuronavigation system and the HoloLens. Each registration on both systems provided a registration transform that was compared for accuracy and consistency. Participant performance was quantified in terms of duration and accuracy for both patient registration and lesion delineation, and compared to expert performance. RESULTS: When using AR both registration and delineation were significantly faster than with conventional neuronavigation (p = 0.02 and p < 0.001, respectively, and p < 0.001 for the total duration), taking 79.23 ± 17.48 and 39.58 ± 39.10 seconds while neuronavigation required 96.61 ± 24.54 and 90.80 ± 44.09 seconds. AR had a registration offset of 3.3mm and 3.4 °, and was more consistent compared to neuronavigation. AR facilitated more accurate and detailed lesion delineation, while neuronavigation often overestimated lesion size. CONCLUSION: Augmented reality provides a faster and more accurate alternative for resection planning. Lesion delineation was more intuitive while retaining high accuracy. Future research should focus on further intraoperative implementations.